Functional design of organizational structures in project management - А. А. Tikhomirov (Вестник университета, 2024)
The article considers the function tracing method that provides project organizational structure systematic construction. Interconnectedness of methodological approaches between organizational design on a company scale and the role-based project structures construction has been described. Based on the existing level of organizational design development and its most frequently used methods, the tracing functions method from the project requirements to the functional roles of a project organizational structure have proposed and formalized. Initial data volume for organizational design and parallels between organizational structures of a company in general and a project in particular have been given. A mathematical scheme of the projected organizational structure functional distribution has been proposed considering a five-stage approach in tracing functions. The approach describes the stages of modeling the project organizational structure. On the basis of distributing the tasks required to be performed during the project realization, the principles description providing the correlation of the functionality to the project roles on the basis of the project realization goals has been offered. The factors that have a positive impact on project implementation and based on the considered approach of organizational structures functional design have been presented.